Empowerment of health cadres in conducting stunting prevention efforts using EMPASI SEHATI educational media - Putri Widita Muharyani; Mutia Nadra Maulida; Karolin Adhisty; Herliawati Herliawati (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2023)
Stunting is one of the nutritional problems experienced by the world, including Indonesia. Stunting occurs due to multifactorial causes. The incidence of stunting increases during the provision of complementary feeding. Many families practice inappropriate feeding practices, including early complementary feeding. Health cadres, as an extension of healthcare workers who interact directly with the community, are important in having the knowledge and ability to educate the community. The purpose of this community service activity is to empower health cadres to accelerate the reduction of stunting prevalence using the EMPASI SEHATI media. There is an increase in the knowledge of health cadres and the community regarding meeting the nutritional needs of children. The EMPASI SEHATI educational media can be an effective media that can be accommodated by health centers to increase public knowledge in the effort to prevent stunting in Indonesia.